(untitled) - Shelton, Claudia Marshall (Hoboken, N.J., 2007)
Blind Spots motivates us to think differently, to push our skills to the next level and openly see and manage our Blind Spots. Claudia Shelton helps us to develop Clear Sight of where we want to go and how to get there. There is a clear difference in my performance level and the increased value I am bringing to the company.
Keywords: Success in business,Executive coaching